Developing a Project-Based Learning Model for Slow Learners in Higher Education - Alhamuddin Alhamuddin; Abdul Rohman; Ahmad Fanani (Jurnal Pendidikan Islam Indonesia, 2022)
This study aims to develop a learning model for slow learner students in Higher Education. Slow learners are students who have low learning achievements under the average, either in one area or in all academic areas. This type of research was research and development using the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The developed learning model was project-based learning. Data collection was conducted through interviews, observations, questionnaires, and tests. Data analysis used two approaches, namely qualitative and quantitative. The results of the study showed that project-based learning due to the activity level had increased compared to before using the PBL model. The result of the coefficient of determination revealed that the value of R square (R2) was 0.064 or 6.4%. This shows that the student activity was able to influence the variation of learning outcomes by 6.4% and the remaining 93.6% was influenced by other variables outside this research model. Thus, it is necessary to have a variety of strategies used by lecturers in delivering lectures, especially in a class where slow learners exist. In addition, attention and assignments also need to be given to slow learners so that they can attend lectures and understand the material presented properly and correctly like other students. For researchers, it is necessary to conduct further studies and research for the development of various learning models that are suitable for the needs of slow learner students.